Predicament of the Hongwu Emperor and his Defense for the Regime's Legitimacy. (3rd July 2021) - Han, Xu; Yan, Xuanjun
Abstract : Known for his shrewd and calculating nature, Emperor Hongwu faced a critical challenge concerning regime legitimacy at the beginning of the Ming Dynasty. At that time, scholars generally adopted a non-collaborative attitude while Zhu's humble origin was despised by the gentry. Using official historical books, intellectuals' commonplace books, and poetry anthologies of that time, this article demonstrates that Zhu Yuanzhang's explanation for the validity of the Yuan-Ming transition comes from the perspective of scholars on the Mandate of Heaven, and reveals that Zhu took a series of measures to solve this crisis by obtaining scholars' support for the Ming court. The textual research in this article, which differs from the focus on policy, law, system, and other perspectives in previous works, offers another approach to the discussion in the field of early Ming Dynasty.